2022
DOI: 10.3390/genes13071249
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis Identifies Candidate Genes Encoding Feather Color in Ducks

Abstract: Comparative population genomics and genome-wide association studies (GWAS) offer opportunities to discover human-driven detectable signatures within the genome. From the point of view of evolutionary biology, the identification of genes associated with the domestication of traits is of interest for the elucidation of the selection of these traits. To this end, an F2 population of ducks, consisting of 275 ducks, was genotyped using a whole genome re-sequence containing 12.6 Mb single nucleotide polymorphisms (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Yang et al [ 25 ] have found that six SNPs of MITF are associated with plumage color in Kaiya–Liancheng F2 offspring. Guo et al [ 51 ] found that MITF is closely related to white plumage color. In this study, we identified three SNPs in MITF (chr13:15411658 A > G , chr13:15412570 T > C , and chr13:15412592 C > G ) in white-feathered ducks, which are located in the intron region.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al [ 25 ] have found that six SNPs of MITF are associated with plumage color in Kaiya–Liancheng F2 offspring. Guo et al [ 51 ] found that MITF is closely related to white plumage color. In this study, we identified three SNPs in MITF (chr13:15411658 A > G , chr13:15412570 T > C , and chr13:15412592 C > G ) in white-feathered ducks, which are located in the intron region.…”
Section: Discussionmentioning
confidence: 99%
“…It activates the TYR core enhancer, which helps to regulate the tyrosinase gene in melanocytes ( Yun et al, 2019 ). At present, the predominant candidate genes related to duck feather color are TYR ( Sultana et al, 2018 ), TYRP1 ( Xi et al, 2020 ), DCT ( Sultana et al, 2018 ), MC1R ( Liu et al, 2023a ), EDNRB2 ( Guo et al, 2022 ), and MITF ( Zhou et al, 2018 ; Lin et al, 2019 ; Wang et al, 2022a ).…”
Section: Discussionmentioning
confidence: 99%
“…DENND4A ( DENN -domain-containing 4A) gene produces a protein that has a DENN domain and plays a role in releasing guanosine diphosphates (GDP) from the small guanine nucleotide-binding proteins (G-proteins) for the formation of guanosine triphosphates (GTP). Additionally, the protein activates ras-related proteins, particularly Rab-10, which regulates intracellular vesicle trafficking [ 45 , 46 ]. The DENND4A gene also contains molecules that are vital for antiviral responses and inflammation, and may play a key role in regulating avian beak and feather disease virus (BFDV) [ 47 ].…”
Section: Discussionmentioning
confidence: 99%